Metode SMART: Dalam Memilih Alat Penangkapan Ikan Tradisional Ramah Lingkungan Bagi Nelayan di Kota Sibolga - Muhammad Dedi Irawan; Rizky Akbar Situmeang; Siska Mayasari Rambe; Yustria Handika Siregar (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The use of the environmentally friendly traditional fishing gear is very beneficial for fishermen in the fishing process. This needs to be implemented as an effort to maintain the sustainability and sustainability of fish resources in the future. This study aims to identify the fishing gear used in Sibolga City and determine the level of environmental friendliness. The criteria in making this decision are having high selectivity (10%), not damaging habitat (25%), producing high-quality fish (15%), not harming fishermen (30%), and production not harming consumers (20%). Based on the research results, the recommendation in the first rank is Payang with a selectivity criterion value of 1, followed by drift and Dogol which have the same value, namely a high selectivity criterion of 0.5. The conclusion of this study is that the Payang, drift, and Dogol fishing gear are classified as environmentally friendly traditional fishing gear using the SMART (Simple Multi-Attribute Rating Technique) method because they can produce catches with high selectivity, minimal habitat damage, high-quality fish production, not harmful to humans. fisherman. themselves and other people around and produce fish that do not harm consumers.